2023
DOI: 10.3389/fnut.2023.1081928
|View full text |Cite
|
Sign up to set email alerts
|

Associations between dietary intake, physical activity, and obesity among public school teachers in Jeddah, Saudi Arabia

Abstract: ObjectiveWe aimed to assess the dietary intake of certain food groups in a representative sample of public-school teachers living in Jeddah city. We also, examined the association of dietary intake with physical activity and obesity among schoolteachers.MethodsThe study was a cross-sectional online survey, conducted among 640 (177 male, 463 female) schoolteachers aged between 20 and 62 years old and working in public primary, intermediate, and high schools in Jeddah. Measurements included gender, weight, heigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 91 publications
0
0
0
Order By: Relevance
“…The aim of acquiring these data is to improve the quality of life of this category of workers by identifying appropriate intervention strategies. Therefore, we carried out this crosssectional study to investigate these aspects that contribute to determining the lifestyle of this class of workers, as previously shown in the literature [28]. According to Gomes et al [47], teachers' positive or negative experiences with physical activity can influence their propensity to create an educational climate that promotes PA and active lifestyles in schools.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The aim of acquiring these data is to improve the quality of life of this category of workers by identifying appropriate intervention strategies. Therefore, we carried out this crosssectional study to investigate these aspects that contribute to determining the lifestyle of this class of workers, as previously shown in the literature [28]. According to Gomes et al [47], teachers' positive or negative experiences with physical activity can influence their propensity to create an educational climate that promotes PA and active lifestyles in schools.…”
Section: Discussionmentioning
confidence: 92%
“…A recent study reported a negative relationship between BMI and food intake in school teachers. In particular, less physically active teachers had unhealthy food habits [28]. The COVID-19 pandemic seems to have influenced this population of workers by favoring or hindering the intake of unhealthy foods [2].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation